Metabolic Factors and Chronic Hepatitis C: A Complex Interplay. (17th July 2013) - Macaluso, Fabio Salvatore; Maida, Marcello; Minissale, Maria Giovanna; Li Vigni, Teresa; Attardo, Simona; Orlando, Emanuele; Petta, Salvatore
Abstract : In the last years, several lines of evidence showed how metabolic factors may influence the natural history of patients with chronic hepatitis C. Chronic HCV infection is able to perturb the metabolic homeostasis of the host, in a context of complex interactions where pre-existent metabolic status and genetic background play an important role, allowing us to state that HCV infection is a systemic disease. In this review, we discuss the most recent lines of evidence on the main metabolic factors that are known to be associated with CHC, namely, insulin resistance/type 2 diabetes, steatosis, visceral obesity, atherosclerosis, vitamin D, menopause, fructose and coffee intake, lipoproteins, methylenetetrahydrofolate reductase status, and hyperuricaemia. In particular, we focus on the pathophysiological mechanisms underlying the correlation between HCV infection and metabolic disorders, the impact of metabolic factors on the progression of liver and non-liver-related diseases, and, on the contrary, the possible influence of chronic HCV infection on metabolic features. In this setting, the importance of a multifaceted evaluation of CHC patients and a prompt correction of modifiable metabolic risk factors should be emphasized.